The use of immersive virtual reality for teaching fieldwork skills in complex structural terrains. (October 2022) - Harknett, J.; Whitworth, M.; Rust, D.; Krokos, M.; Kearl, M.; Tibaldi, A.; Bonali, F.L.; Van Wyk de Vries, B.; Antoniou, V.; Nomikou, P.; Reitano, D.; Falsaperla, S.; et al.
Abstract: Innovations in virtual reality (VR) technology have led to exciting possibilities in teaching earth sciences, allowing students to experience complex geological sites that, due to cost and logistical reasons, they would not normally be able to experience. The need for high quality online digital learning resources and blended learning was brought to the forefront during the SARS-CoV-2 pandemic, as courses with a traditional physical field work component were forced to move online and provide alternatives to students. While it is unlikely that virtual field trips (VFT) would be accepted by students as a replacement of real-world fieldwork moving out of the pandemic, research shows promise that using IVR experiences can lead to enhanced learning outcomes in geosciences, warranting its inclusion on the curricula. This paper presents the outputs of a project to improve student learning in complex geological environments using VR. Here we outline a workflow that was developed to collect high resolution imagery using remote sensing to create digital outcrop models (DOM) of complex geological sites. Using this framework, this paper will then explore the use of VR for an investigation of the Husavik Triple Junction, a complex structural site in northern Iceland, explaining how the drone data was converted to a 3D DOM and demonstrating how VR can be used to simulate real world field mapping. Finally, we describe how these IVR activities have been integrated into taught modules at postgraduate level and discuss how the use of IVR experiences can complement existing geoscience curriculum design. Highlights: Describes the use of immersive virtual reality models for teaching in complex structural terrains. . Describes a unique case study of a subaerial triple junction, near Husavik in Iceland . Describes best practises for implementing virtual reality in existing geoscience curricula . Provides links to freely available software tools, VR data and teaching materials for the Husavik site.